Peningkatan Pemahaman Dan Partisipasi Keagamaan Masyarakat Melalui Program Kajian Islam Interaktif di SMA Negeri 1 Sukapura Probolinggo - Arif Rahman; Sulastri Sulastri (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The Interactive Islamic Studies Program at SMA Negeri 1 Sukapura was developed to enhance the religious understanding and participation of students and the community amid the challenges of modernisation that affect the spiritual life of young people. This program integrates participatory learning methods and digital da'wah to make religious activities more communicative, engaging, and relevant to participants’ needs. This community service initiative employed the Participatory Action Research (PAR) method through the stages of planning, action, observation, and reflection, with data collected through participatory observation, interviews, and documentation. The results indicate a significant improvement in students’ knowledge of aqidah, akhlak, and practical fiqh, along with positive behavioural changes in their daily lives. Community participation increased consistently, marked by collaborative involvement among teachers, students, religious leaders, and residents. The utilisation of social media, live streaming, and digital learning materials expanded the outreach of da'wah and strengthened youth engagement. Overall, the program proved effective as an inclusive and sustainable school-based model of religious development.